APLIKASI SISTEM INFORMASI GEOGRAFIS UNTUK MEMETAKAN DISTRIBUSI SASARAN PEMANTAUAN KESEHATAN IBU DI WILAYAH KERJA PUSKESMAS I DENPASAR SELATAN - Kurniasari, Ni Made Dian; astuti, Putu Ayu swandewi; Widarsa, Tangking; Mulyawan, Hari (ARCHIVE OF COMMUNITY HEALTH; Vol 1 No 1 (2012): Juni (2012)DO - 10.24843/ACH.2012.v01.i01.p04)
Indonesian Maternal Mortality Rate (MMR) in 2007 was 228 per 100.000 live births. A program to reduce MMR was Local Area Monitoring of Maternal Health and was conducted by Public Health Centers (PHCs) throughout Indonesia. This study aims to apply geographic information system (GIS) as a tool to provide maps which describe the target of local area monitoring of maternal health, the distribution of maternity health centers, and level of poverty in the catchment area of South Denpasar I PHC in November to December 2010. This study used descriptive research with a cross sectional approach. Samples were pregnant women, mothers that had giving birth and maternity health centers in the catchment area of South Denpasar I PHC from November to December 2010. The results showed GIS can be used to create maps to describe various data of maternal health that relates to Local Area Monitoring. The type of maps that were generated for this study were choropleth maps, dot density maps, point location maps, a combination of choropleth maps with point location maps and bu? ering maternity health center maps. The recommendation is that PHCs should consider using GIS as a tool for presenting data related to local area monitoring of maternal health. More advanced uses of GIS as a tool to analyze data and to visualize the results of other research which is related to maternal health and geographic conditions is worth exploring.
Keywords: Local Area Monitoring of Maternal Health, GIS, Maternity Health Center and Poverty level.